The Influence of Guided Writing Materials Toward Students’ Writing Ability of the Fifth Semester Students at English Study Program FKIP UR - Salwa Salwa; Kurniati Kurniati (Universitas Muhammadiyah Tangerang, 2020)
This study investigated the influence of guided writing materials in students’ writing ability at English Study Program FKIP UR in which forty students that simple randomly selected at English Study Program FKIP UR. The instruments used were questionnaire and writing test. Based on the research findings, the responses of questionnaire were coded into interval score by using Likert Scale which showing the students’ ability and their opinion in guided writing that consisted of fifteen statements based on six indicators in the form of frequency. On the other side, writing test administered in term of finding the students’ writing ability. It was a writing outlining with fifteen listed in the form of brief statements. Before the research revealed, the tried out had been applied in assessing the validation of the instrument by using Pearson Product Moment correlation formula indicated that items were valid. Reliability calculation were performed in Cronbach’s Alpha denoted that the instrument was reliable. The instrument can be stated reliable when if it has Cronbach Coefficient is higher than 0.60. based on research findingsm it can be concluded that: first, the students’ writing by using guided writing was categorized into good category 56.2, second, the mean score of students’ writing test is 50.68, it can be stated that students’ writing ability is categorized into good category. While Fcount is 27.78 and Ftable is 4.25. Based on its criteria, H0 is accepted if Ftable < Fcount and Ha is accepted if Fcount > Ftable. After it compared (27.78 > 4.25), it showed that H0 is rejected. It can be concluded that there was significant influence of guided writing in students’ writing ability.